Contextual factors of teachers’ wellbeing: two Italian case studies - Gabola, Piera; Iannaccone, Antonio (Swiss Journal of Educational Research, 2018)
The article provides a reflection on some critical components featuring teachers’ professional well-being construction. In addition to the known causes of the burnout onset such as individual, emotional, and relational factors, the effects that appear to be related to working conditions in its whole and, therefore, the system in which  the job is carried out, are considered. To examine these effects, the article describes the results of two empirical studies independently conducted in the Italian school system. Particularly, the two studies focus on the conditions of social and professional well-being of nursery and primary schools teachers at two distinct periods of the Italian school system evolution. During the ten years lasting between the two studies, this school system has been affected by continuous reform attempts, by temporary work increase, by a progressive weakening of the social recognition of the profession, by the widespread presence in the classroom of children belonging to different cultures, by the introduction of new technologies, and by the discrepancy between future teachers’ expectations and their actual job. The reconsidering of these two study results on burnout, though they partly confirm the results of other similar researches, raises the further question with respect to the contextualization of the teachers’ discomfort expression in relation to the wider professional identity weft in which they operate. This weft seems to change with the changing of social and cultural education.